Finalitas Kekristenan dan Argumentasinya yang Final - Stevri Indra Lumintang (Jurnal Missio Cristo, 2019)
Abstract: No religion could ever deny the fact that there is an element of religious plurality and its influences in a plural society. Each religion possesses a claim on the finality or uniqueness of the Lord they worship and believe in. Among the Christians living in a Christian majority society, the topic of "the finality of Christ and Christianity" is no of an interest to them. This is because they are living in a "safe zone". However, where they are a minority in a society such topic is taboo and they are prohibited to talk about it for fear of "intimidation" from the majority. This article is written with the view of putting forwards four arguments on the claim of "the finality of Christianity". These are namely psychological, theological, missiological, and historical. These arguments give some implications to strengthen the faith of Christians and thereby to cause them to be more passionate in loving their God and neighbours.